Assessing Central Bank Credibility During the EMS Crises : Comparing Option and Spot Market-Based Forecasts - Markus Haas; Stefan Mittnik; Bruce Mizrach (Rutgers University, Department of Economics, 2004)
Financial markets embed expectations of central bank policy into asset prices. This paper compares two approaches that extract a probability density of market beliefs. The first is a simulated moments estimator for option volatilities described in Mizrach (2002); the second is a new approach developed by Haas, Mittnik and Paolella (2004a) for fat-tailed conditionally heteroskedastic time series. We find, in an application to the ERM crises of 1992-93, that both the options and the underlying exchange rates provide useful information for policy makers.
Keywords: G12; G14; F31; 330; options; implied probability densities; GARCH; fat-tails; European Monetary System; Geldpolitik; Glaubwürdigkeit; Erwartungstheorie; Devisenoptionsgeschäft; Optionspreistheorie; Europäischer Währungsverbund; Statistische Verteilung; ARCH-Modell; EU-Staaten